2009
DOI: 10.1007/s00775-009-0604-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein recognition in ferredoxin–P450 electron transfer in the class I CYP199A2 system from Rhodopseudomonas palustris

Abstract: CYP199A2 from Rhodopseudomonas palustris CGA009 is a heme monooxygenase that catalyzes the oxidation of para-substituted benzoic acids. CYP199A2 activity is reconstituted by a class I electron transfer chain consisting of the associated [2Fe-2S] ferredoxin palustrisredoxin (Pux) and a flavoprotein palustrisredoxin reductase (PuR). Another [2Fe-2S] ferredoxin, palustrisredoxin B (PuxB; RPA3956) has been identified in the genome. PuxB shares sequence identity and motifs with vertebrate-type ferredoxins involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…The first electron transfer is rate limiting for a number of bacterial P450 systems including P450 cam (CYP101A1) from Pseudomonas putida (Brewer and Peterson, 1988), CYP199A2 and CYP199A4 from Rhodopseudomonas palustris (Bell et al, 2010b(Bell et al, , 2010c) and CYP101D1 from Novosphingobium aromaticivorans Bell et al, 2010a;Yang et al, 2010). It has been shown that the first flavin-to-heme electron transfer, though one of the slower steps in the overall catalytic cycle, is not rate limiting for palmitate and arachidonate oxidation by P450 BM3 (Munro et al, 1996;Ost et al, 2003;Whitehouse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The first electron transfer is rate limiting for a number of bacterial P450 systems including P450 cam (CYP101A1) from Pseudomonas putida (Brewer and Peterson, 1988), CYP199A2 and CYP199A4 from Rhodopseudomonas palustris (Bell et al, 2010b(Bell et al, , 2010c) and CYP101D1 from Novosphingobium aromaticivorans Bell et al, 2010a;Yang et al, 2010). It has been shown that the first flavin-to-heme electron transfer, though one of the slower steps in the overall catalytic cycle, is not rate limiting for palmitate and arachidonate oxidation by P450 BM3 (Munro et al, 1996;Ost et al, 2003;Whitehouse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These oxygenases are important in drug metabolism and can perform specific chiral introduction of functional groups. Cytochrome P450-199A2 from Rhodopseudomonas palustris oxidizes para-substituted benzoic acids and has an associated [2Fe-2S] ferredoxin, palustrisredoxin, rather than ferredoxin [9]. Expression of a similar P450 in E. coli from a tricistronic construct generated a whole cell biocatalyst that efficiently oxidized (1R)-(+)-camphor to 5-exo-hydroxycamphor and limonene to (-)-perillyl alcohol [10].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
“…Some examples illustrating the requirement for cofactor balance and availability include: the conversion of biomass feedstocks containing xylose to ethanol where the formation of xylitol is a problem [1][2][3][4][5][6][7]; as a driving force for more effective production of reduced compounds such as biofuels [8]; in using cytochrome P450s in specific oxidation reactions where the recycling of active enzyme is required [9][10][11]; and the production of chiral pharmaceutical intermediates where specific reductions require a certain cofactor [12,13]. Experimental studies along with more complete computational models have shown a global picture of the flow of reducing equivalents and its connection to cell physiology and allowed these insights to be considered for metabolic engineering purposes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[9,15,22] with a set of spectra generated from the sum of the appropriate percentages of the spectra of the substrate-free (>95% low-spin, Soret maximum at 418 nm) and camphor-bound (>95% high-spin, Soret maximum at 392 nm) forms of WT CYP101A1.…”
Section: Enzymes and Molecular Biologymentioning
confidence: 99%
“…[6,7] The high enzymatic activity of CYP199A4 with this substrate is supported by a class I electron transfer chain consisting of a [2Fe-2S] ferredoxin (HaPux) and a flavin-dependent ferredoxin reductase (HaPuR) which mediate heme reduction by NADH. [1,[8][9][10] The stable, soluble nature and high activity of bacterial CYP enzymes, such as CYP199A4, results in them being of interest for applications in synthetic chemistry involving C-H bond oxidation. [11,12] Furthermore, these enzymes can be engineered via rational mutagenesis or directed evolution to enhance their activities and broaden their substrate range.…”
Section: Introductionmentioning
confidence: 99%